The structure of mangrove communities in response to water quality in Jakarta Bay, Indonesia - NILAM SARI; MUFTI P PATRIA; TRI EDHI BUDHI SOESILO; IWAN GUNAWAN TEJAKUSUMA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sari N, Patria MP, Soesilo TEB, Tejakusuma IG. 2019. The structure of mangrove communities in response to water quality in Jakarta Bay, Indonesia. Biodiversitas 20: 1873-1879. The waters of Jakarta Bay, which is a habitat for mangrove vegetation, have been polluted caused by many human activities such as development of housing, industry, tourism and facilities along the coast, and reclamation of man-made islands. The islands reclamation has caused changes in ocean current pattern and has impacts on material mobilization in the waters. The mangroves have experienced degradation as well since long time ago. The purpose of this research was to investigate the responses of mangrove vegetation to the quality of water in disturbed areas in Jakarta Bay to be used as baseline information for mangrove forest management in the area. Analysis of vegetation was used to examine mangrove community structure with the results were then related to the measurements on water quality using simulation modeling. The results show that mangrove forests in Jakarta Bay have an average Important Value Index (IVI) for all levels of life stage 95.7% with relative density of 28.85%, relative frequency of 29.21%, and closure relative of 38.62%. These results indicate that the mangrove forests in Jakarta Bay are under the criteria of damaged or disturbed according to the Minister of Environment Regulation. The mangrove forests were dominated by Avicennia marina, Avicennia lanata, Rhizophora apiculata, Sonneratia caseolaris, and Sonneratia alba. The average of ocean current velocity was 0.04-0.08 m/s. tides were single type with short waves generated by wind. The water discharge from 13 rivers were 205 ± 97 m3/s and the water discharge from power plant 224.9 m3/s. The heavy metal whereas The average pH was 7.75; Dissolved Oxygen 4.68 mg/L; turbidity 5 m; Total Suspended Solid (TSS) 50.95 mg/L; and salinity 6.6 ‰. The result of grain size analysis showed that most sediments obtained was in the form of silt with a mixture of little clay and sand. The responses showed that there was a reinforced pattern for pH, temperatures, rainfall, brightness, sediment, DO, and ocean current, with a trend of exponential growth in two years next of important value index of mangroves in response to water quality in Jakarta Bay. The heavy metals of Pb have concentrations of 65-104 ppm in sediments and 38-60 ppm in the water column; Zn has 150-258 ppm in sediment and 42-140 ppm in water column; Cu has 34-72 ppm in sediment and 13-30 ppm in water column; Ni has 33-39 ppm in sediment and 40-50 ppm in water column; Cd has 5.9-8 ppm in sediment and 8.5-15 ppm in the water column. The heavy metals, TSS, and water river discharge have balance-decay pattern. The amount of river water discharge entering Jakarta Bay, the heavy metals, and the low level of ocean currents cause coastal waters of Jakarta Bay to become muddy puddles that cannot flow properly. These conditions make the mangrove forest habitat becomes polluted and the mangrove vegetation degraded. Therefore, all of these things need to get serious attention so the mangrove forests can be restored and the function of mangroves can return to normal.